The Ad Blocking Wars. - MURPHY, KATE (New York Times, 2016)
The article examines the increasing number of Internet users who are using ad blocking software as of February 2016, dealing with topics including the impact of online advertising on the Internet surfing experience and web publishers' efforts to stop developers from creating ad blockers.